2020
DOI: 10.1590/1678-992x-2018-0373
|View full text |Cite
|
Sign up to set email alerts
|

Practicability of somatic cell count and electrical conductivity as subclinical mastitis diagnostic tests in camels (Camelus dromedarius)

Abstract: Critical gaps exist in our understanding of the diagnostic reliability of subclinical mastitis tests in dromedary camels. Using a retrospective longitudinal cross-sectional approach, 191 lactating camels were randomly sampled from 47 camel herds to investigate at first the practicability of somatic cell count (SCC) and electrical conductivity (EC) tests as subclinical mastitis tests in camels through their validations by California mastitis test (CMT) score, and then through the subsequent employments of those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, the sole element that affected Wadha camels was parity. The SCC test has been demonstrated to be valid and reliable for diagnosing SCM in dromedary camels since it is widely used as a measure of udder health and milk quality (Qayyum et al 2026;Jadhav et al 2018;Aljumaah et al 2019;Sumon et al 2020 andMohamed et al 2022). According to Seligsohn et al (2020), milk bacterial screening is the most reliable method for diagnosing SCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the sole element that affected Wadha camels was parity. The SCC test has been demonstrated to be valid and reliable for diagnosing SCM in dromedary camels since it is widely used as a measure of udder health and milk quality (Qayyum et al 2026;Jadhav et al 2018;Aljumaah et al 2019;Sumon et al 2020 andMohamed et al 2022). According to Seligsohn et al (2020), milk bacterial screening is the most reliable method for diagnosing SCM.…”
Section: Discussionmentioning
confidence: 99%
“…Because changes in the udder tissue occur before they become noticeable, early identification of SCM is essential. Aljumaah et al (2019) have demonstrated that the somatic cell count (SCC) is a valid and dependable diagnostic for detecting SCM in dromedary camels. Somatic cells proliferate because a defense mechanism against invading pathogens is produced by mammary epithelial cells, which sense their ligands and trigger the proper immune responses (Mohsin et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, milk samples having >300x10 3 cells/mL were considered high SCC and likely to be obtained from udders with subclinical mastitis. A study by Aljumaah et al (2019) demonstrated the reliability and validity of the SCC test in distinguishing subclinical mastitis in dromedary camels. The study suggested that 472.50×10 3 cells/mL is a logical SCC reading for herd management decisions.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study by Jadhav et al (2018) reported that the cut-off for distinguishing subclinical mastitis cases in cattle from healthy ones was 310,000 cells/mL of milk. In camels, Aljumaah et al (2019) reported that the threshold for separating camels with sub-clinical mastitis from normal ones was 472,500 cells/mL of milk.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of subclinical mastitis in dairy camels varies across different regions and is influenced by various risk factors such as the number of parities, lactation stage, and production system (Ahmad et al, 2012; Aljumaah et al, 2020). According to a review study, during the last decades, cases of mastitis in dromedary camels have been reported from many of the camel-rearing countries of Africa and Asia, such as Kenya, Somalia, Sudan, Egypt, Saudi Arabia, Iraq and UAE (Abdelgadir, 2014).…”
Section: Introductionmentioning
confidence: 99%